Mass spectrometry-based proteomic exploration of the small urinary extracellular vesicles in ANCA-associated vasculitis in comparison with total urine - Prikryl, Petr; Satrapova, Veronika; Frydlova, Jana; Hruskova, Zdenka; Zima, Tomas; Tesar, Vladimir; Vokurka, Martin (Journal of proteomics, 2021)
ANCA-associated vasculitis (AAV) is a rare, but potentially severe autoimmune disease, even nowadays displaying increased mortality and morbidity. Finding early biomarkers of activity and prognosis is thus very important. Small extracellular vesicles (EVs) isolated from urine can be considered as a non-invasive source of biomarkers. We evaluated several protocols for urinary EV isolation. To eliminate contaminating non-vesicular proteins due to AAV associated proteinuria we used proteinase K treatment. We investigated the differences in proteomes of small EVs of patients with AAV compared to healthy controls by label-free LC-MS/MS. In parallel, we performed an analogous proteomic analysis of urine samples from identical patients. The study results showed significant differences and similarities in both EV and urine proteome, the latter one being highly affected by proteinuria. Using bioinformatics tools we explored differentially changed proteins and their related pathways with a focus on the pathophysiology of AAV. Our findings indicate significant regulation of Golgi enzymes, such as MAN1A1, which can be involved in T cell activation by N-glycans glycosylation and may thus play a key role in pathogenesis and diagnosis of AAV. SIGNIFICANCE: The present study explores for the first time the changes in proteomes of small extracellular vesicles and urine of patients with renal ANCA-associated vasculitis compared to healthy controls by label-free LC-MS/MS. Isolation of vesicles from proteinuric urine samples has been modified to minimize contamination by plasma proteins and to reduce co-isolation of extraluminal proteins. Differentially changed proteins and their related pathways with a role in the pathophysiology of AAV were described and discussed. The results could be helpful for the research of potential biomarkers in renal vasculitis associated with ANCA.
Keywords: extracelulární vezikuly; ANCA-asociované vaskulitidy; N-glycosylation; Extracellular Vesicles; Proteomics; tandemová hmotnostní spektrometrie; Small extracellular vesicles; Proteinuria; Urinary proteomics; Humans; proteomika; Chromatography, Liquid; Tandem Mass Spectrometry; ANCA-associated vasculitis; chromatografie kapalinová; Exosomes; lidé; Anti-Neutrophil Cytoplasmic Antibody-Associated Vasculitis